Female Sterilization by Tubal Ligation During C-Section in Women with a History of 2 or More C-Section - Kansu Celik, Hatice; Uygur, Dilek; Tasci, Yasemin; Durmus, Merve Gulsen; Kisa Karakaya, Burcu; Engin Ustun, Yaprak (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: The aim of this study is to determine bilateral tubal ligation incidence performed during C-section in women with a history of 2 or more C-section and the factors affecting sterilization demand. Study Design: Patients who were admitted to Zekai Tahir Burak Woman’s Health, Education and Research Hospital between February 2017 and June 2017 and who had a history of 2 or more C-section between week 37 and 41 were included in this prospective cross-sectional study. These subjects were separated into 2 groups according to whether they wanted bilateral tubal ligation during C-section. Bilateral tubal ligation was performed by means of modified Pomeroy technique. Both groups were compared in terms of age, gravida, number of children living at home, education level and income status. Patients who did not want bilateral tubal ligation were asked to fill a questionnaire involving reasons for not asking for bilateral tubal ligation. Results: The number of patients who wanted bilateral tubal ligation was 51 (43%) while those who did not want bilateral tubal ligation was 67 (57%). Compared with patients who did not want bilateral tubal ligation, patients who wanted bilateral tubal ligation had more number of children at home and a higher number of previous C-section (p<0.001). Reasons for not wanting bilateral tubal ligation consisted of religious beliefs (26.8%), desire for protection with a reversible contraceptive method (17.9%), partner who does not want bilateral tubal ligation (17.9%), incompletely family size (13.4%), respectively according to their frequency. Conclusion: bilateral tubal ligation for contraception during C-section was performed forty-three percent of women who had had a history of 2 or more C-section. In one fourth of the cases, pregnant women did not want bilateral tubal ligation due to religious beliefs.